Light and Scanning Electron Microscopy of Red Blood Cells From Humans and Animal Species Providing Insights into Molecular Cell Biology - Benga, Gheorghe; Cox, Guy (Frontiers in Physiology, 2022)
We reviewed the many discoveries in cell biology, made since the 17th century, which have been based on red blood cells (RBCs). The advances in molecular and structural biology in the past 40 years have enabled the discovery with these cells, most notably, of the first water channel protein (WCP) called today aquaporin1 (AQP1). The main aim of our work reviewed was to examine by light and electron microscopy a very wide range of RBCs from reptiles, birds, monotremes, marsupials and placentals, in order to estimate from these images the RBC cell volume and surface area. The diffusional water permeability of the RBC membrane from these species has further been measured with a nuclear magnetic resonance (NMR) spectroscopy technique. The significance of the observed permeability of RBCs to water and possible influences on the whole body are discussed.